INFORMASI BENCANA & BUDAYA KOMUNIKASI LOKAL Kasus Bukit Duri Jakarta Selatan - Somo Arifianto; Mohan Rifqo Virhani (Jurnal Masyarakat Telematika dan Informasi, 2010)
This article is a part of the study Effectiveness of Information Dissemination for Disaster area, and conducted by Research and Development APTEL SKDI years 2009. The area of South Jakarta Bukit Duri in this case study because it is unique. Residents location of Bukit Duri on the banks of ci/iwung rivers. Despite living near in the middle of metropolis almost no information as expected. The level of awareness of hygiene and environmental regulation is relatively low. The results of this study indicate that the information flood is still required, is considered important as a guide to the locals' knowledge. They understand not only formally, but also read symbols and natural phenomena. While the most dominant search and distribute information on flood disaster is television. In addition to interpersonal media are also personal because it has a closeness with the people of Bukit Duri.